Climate change and public health in Germany – An introduction to the German status report on climate change and health 2023 - Elke Hertig; Iris Hunger; Irena Kaspar-Ott; Andreas Matzarakis; Hildegard Niemann; Lea Schulte-Droesch; Maike Voss (Journal of Health Monitoring, 2023)
Global warming of 1.5°C and even 2°C is likely to be exceeded during the 21st century. Climate change poses a worldwide threat and has direct and indirect effects on infectious diseases, on non-communicable diseases and on mental health. Not all people are equally able to protect themselves against the impacts of climate change; particularly populations that are vulnerable due to individual factors (children, older persons, those immunocompromised or with pre-existing conditions), social factors (the socially disadvantaged), or living and working conditions (e. g. people who work outdoors) are subject to an increased risk. Concepts such as One Health or Planetary Health provide a framework to frame both climate change itself and adaptation strategies or sets of actions for environmental human and animal health. Knowledge of climate change impacts has grown in recent years, and mitigation and adaptation strategies have been developed.